Internationalized armed conflicts - an analytical study in light of the rules of international humanitarian law - Abbo, Abdullah Ali (Journal of Legal and Political Studies, 2015)
It is well known that the armed conflict in international humanitarian law mainly classified into two types, the first type is the armed conflict which has international nature (international armed conflicts), and the second type is the Armed conflicts which has not international character (internal armed conflict), it has been mentioned in the Hague Conventions ( 1899-1907) and the four Geneva agreements (1949) and the two additional Protocols (1977), in addition to the customary rules of international humanitarian law, the provisions and rules that apply to these types of armed conflicts in its various forms, and that the parties to the conflict should restrict it in order to protect the victims of these conflicts in one hand, and to protect the money and objects that are not legitimate military targets on the other hand, thus there is no problem regarding the international regulation of armed conflict (international and internal) and also the humanitarian rules applicable to them, but in the recent years there has resulted_ because of international practices and the conflicts appeared in the world in different parts_ a new type of conflicts (non What we have mentioned), those that are called in the literature and the writings of international law (armed conflict internationalized ), so what is the meaning of these conflicts and what are the legal nature for it and what are the rules that apply to them, this will take up by our searching through two sections, the first one will be about definition of these conflicts and it’s legal nature, and the second will be for models of internationalized armed conflict and the applicable rules on them.
Keywords: armed conflict; international humanitarian law; customary rules; International law